The integration of ICT in HR functions: the impact on operational performance - Benachour, Amira; Tarhlissia, Lamine; Abdelmalek, Hanane; Cheriti, Yasmine (Management and Entrepreneurship: Trends of Development, 2024)
The transition to digital technology marks our shift from the industrial era to the information age, with Information and Communication Technologies (ICT) being at the core of this transformation. ICT is now ubiquitous in our daily lives, and its use continues to grow, profoundly changing the ways we communicate, learn, and work. In light of this exceptional development, it is crucial to understand its impact on organisational practices and operations. Formerly, team managers held onto information and shared it at their discretion. Communication followed the established rules, and the flow of information was dictated by hierarchy. The advent of ICT has isrupted these traditional methods, enabling easier sharing and faster dissemination of information, as well as instant communication. This article examines the impact of Information and Communication Technologies (ICT) on operational performance, focusing on their integration into the human resources (HR) function at Algérie Télécom. The objective is to assess how these technologies influence HR practices and employee management within the company. The methodology is based on a survey conducted among 15 employees from the marketing department of Algérie Télécom, randomly selected. A structured questionnaire was used to collect quantitative data on the perception and use of ICT. Additionally, semi-structured interviews were conducted with the directors of the marketing and communication departments to gather qualitative insights. The data were analyzed using SPSS software to examine the relationships between age, professional experience, and ICT usage. The results show that ICT is widely perceived as a tool that facilitates daily work. It is used to automate administrative data processing, enhance decision-making, and streamline communication between departments. About 72.7% of the employees surveyed confirm that ICT plays an important role in supporting managerial decisions and accomplishing administrative tasks. Moreover, 81.8% of respondents highlight the existence of specific software for various management functions. Access to both internal and external information is also seen as significantly improved due to these technologies. However, several barriers to optimal ICT usage were identified, including a lack of training and limited access to certain tools. Some managers also pointed out that managing these technologies on a large scale is challenging, particularly due to the size of the company and the number of employees involved.Jel Сlassification: M54, O32